Music preference among music degree students in UiTM / Joshua Athur James - James, Joshua Athur (Faculty of Music, 2009)
The purpose of this study was to investigate musical styles as a function of preference, specifically popular music and Western classical music among undergraduate music education, performance and composition students in local university in Klang Valley. Subject were 60 undergraduate student of which there were 20 music education students from parts one to eight, and 20 each students from parts one six for music performance and composition students. The questionnaires were distributed stratified sampling to student who agreed to participate in the study. This study measured preference by using an instrument that consisted of 20 musical examples representing the generic styles of classical and current popular music. The current popular music was selected from music charts such as the Top 10. Subjects indicate preference on a 7-point Likert-type scale. Result showed that, there is a significant difference between both genders. Findings also showed that females have a high preference rating for both of the musical style rather than males. Results also showed that there are significant differences between music education, music composition and music performance students. Music performance programme showed the highest mean compare the other programme for pop music and classical music.